PRACTICAL MEASURING METHOD OF THE EARTH RESISTANCE - MILLY, Miron (Trends in education, 2010)
The paper deals with a simple and practical measuring method of the contact resistance of grounding electrode by using two auxiliary measuring electrodes, with together with the grounding electrode form the system of three electrodes.
Keywords: measuring; contact resistance; electrode; grounding; earth; ground; soil.